Association of mitochondrial DNA polymorphisms and/or haplogroups with elite Japanese athlete status - Noriyuki Fuku; Eri Mikami; Masashi Tanaka (Japanese Society of Physical Fitness and Sports Medicine, 2013)
A number of familial and twin studies have assessed the relative contribution of genetic and environmental factors to physical performance or its-related traits and have estimated that there is a significant genetic component to their phenotypes. In addition, aerobic capacity has been found to have stronger maternal inheritance than paternal. This finding implies that functional differences in maternally inherited mtDNA-encoded proteins involved in oxidative phosphorylation affect aerobic performance. In this article, therefore, we focus on associations between mtDNA polymorphisms/haplogroups and elite Japanese athlete status. From sequencing analysis of the control region in the mtDNA, certain mtDNA polymorphisms and haplogroups were shown to be associated with elite Japanese endurance athlete status, probably due to enhanced ATP production by mitochondria in the cardiac and skeletal muscles or both. This phenomenon is in agreement with several previous reports on Caucasian and African populations. It should be noted that certain mtDNA polymorphisms or haplogroups are also associated with elite Japanese sprint athlete/power status, probably due to enhanced calcium dynamics in the skeletal muscle. Thus, mtDNA polymorphisms/haplogroups influence not only aerobic performance but also anaerobic performance.